2019
DOI: 10.3390/ma12121998
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Electrolytes Development in Dye-Sensitized Solar Cells

Abstract: Dye-sensitized solar cells (DSSCs) have been intensely researched for more than two decades. Electrolyte formulations are one of the bottlenecks to their successful commercialization, since these result in trade-offs between the photovoltaic performance and long-term performance stability. The corrosive nature of the redox shuttles in the electrolytes is an additional limitation for industrial-scale production of DSSCs, especially with low cost metallic electrodes. Numerous electrolyte formulations have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
146
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(147 citation statements)
references
References 429 publications
(932 reference statements)
0
146
0
1
Order By: Relevance
“…Since every part of the cell contributes to the overall performance of a DSC, optimization of semiconductors [9][10][11][12][13], sensitizers [14][15][16][17][18][19][20], counter electrodes [21][22][23], and electrolytes [16,[24][25][26][27][28][29][30][31][32] are all critical. The most widely used sensitizers with photoconversion efficiencies (PCE) of up to 11% are ruthenium-oligopyridine complexes [16,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since every part of the cell contributes to the overall performance of a DSC, optimization of semiconductors [9][10][11][12][13], sensitizers [14][15][16][17][18][19][20], counter electrodes [21][22][23], and electrolytes [16,[24][25][26][27][28][29][30][31][32] are all critical. The most widely used sensitizers with photoconversion efficiencies (PCE) of up to 11% are ruthenium-oligopyridine complexes [16,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, tuning of electrolyte composition can also remarkably enhance the PCE and, as shown for other dyes [31], has the potential to make iron-sensitizers a promising alternative to ruthenium-based compounds. It has been demonstrated that both the redox couple and the components of the electrolyte have a critical influence on the PCE, and this effect originates from its role as a charge transfer medium [32,47]. In this investigation, we focus on the electrolyte However, the use of metals with low natural abundancies significantly increases the cost and sustainability of DSCs [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic devices including batteries, [20] transistors, [21,22] solar cells, [23][24][25] and electrochromic devices (ECDs) have been prepared using thermo-or photocurable solid-gel polymer electrolytes. [19,[26][27][28][29][30][31][32][33][34][35][36] The challenge to generate promising ECDs is complex.…”
Section: Introductionmentioning
confidence: 99%
“…However, solid-state electrolytes with highly crystalline polymers show lower mobility and ionic conductivity than liquid-state electrolytes. To reduce the polymer crystallization, additional inorganic nanofillers can be introduced [17]. In addition, this improves the free volume, thereby improving the ion conductivity and mobility of the solid electrolyte [18].…”
Section: Introductionmentioning
confidence: 99%